Estudo farmacológico de extratos secos padronizados das cascas do caule de Aspidosperma marcgravianum Woodson coletadas na Amazônia Ocidental - (:unkn) unknown (Universidade Federal do Amazonas, 2012)
Aspidosperma marcgravianum Woodson (Apocynaceae) is popularly known as carapanaúba a high quality wood. The bark is used in the Amazonian folk medicine as infusion to treat malaria, diabetes, gastrointestinal disturbances, in uterus and ovarian inflammation, against cancer and as contraceptive. The few papers available do not confirm the folk use, but the about 50 known indolic alkaloids isolated from A. marcgravianum are often used to explain the toxic effect on Artemia franciscana and the described anti-bacterial activity. The present work aimed to study the in vivo and in vitro effects and mechanisms of action of the alkaloids extracted from Aspidosperma marcgravianum. The bark was extracted with ethanol in Soxhlet apparatus generating the ethanol extract (EETOH, 3% yield). The EETOH was partitioned with chloroform in different pH, yielding the chloroform fraction (FCHCl3); further partition yielded the total alkaloids fraction (TAF). FCHCl3 purification in silica gel column chromatography (CC) yielded six fractions of different alkaloids (F13-23, F24-32, F55-73, F33-43, F44-54 and F74-76). FAT standardization in HPLC showed 11 major peaks with retention times from 3.5 to 27.0 min similar to those obtained for the purified fractions. To know the main pharmacological effects induced of A. marcgravianum, mice were orally treated with EETOH and TAF (1 g/kg). EETOH produced evident muscular relaxation and reduced mice motility, as well as dyspnea; death was not observed within 24 h. Comparatively, TAF produced faster and more intense effects that killed all the animals. In rat isolated atrium, FAT (10 to 100 μg/mL) produced negative chronotropic effect related to the drug concentration, positive inotropic effect at low concentration but contraction inhibition at high one. The diaphragm muscle contractions were potentiated by TAF; this action was neither related to an anticholinesterase activity nor to Ca2+-ATPase inhibition. The diaphragm tetanus after repetitive electrical stimulation (30-50 Hz) was not sustained in presence of FAT (10 to 100 μg/mL) but the initial muscle responses were not proportionally blocked; similar effects were observed for the purified fractions at 1 μg/mL. Since the alkaloids did not induce muscle contracture, neither inhibited SERCA 1 activity, nor reduced the initial responses upon repetitive muscle stimulation, the effect on contraction might putatively be explained by increased action potential duration. This effect would increase the muscle membrane refractoriness and would block the tetanus responses, but at the same time it would increase the myofibrils active state resulting in increased contraction of diaphragm and heart muscles. Usually increased action potential duration is due to potassium channel blockade. The present experiments, however, do not provide any direct evidence for this latter effect.
Keywords: Carapanaúba; Aspidosperma marcgravianum; Apocynaceae; CIÊNCIAS BIOLÓGICAS